Dynamic Response of Gradient Foams - Hu, L.L.; Liu, Y. (Проблемы прочности, 2014)
The Voronoi-type density-gradient foams with three layers are numerically simulated, in order to study their dynamic response. The focus of the study is not only on the energy absorption and the distal stress of the gradient foam, but also the impact stress. The results obtained show that reduction of both the initial impact peak stress, and the early energy absorption of the gradient foam can be privided by reducing density of the first layer. The undesirable effect on the energy absorption can be alleviated by diminishing the thickness of the first layer. The difference between densities of the first two layers density should be limited to a certain range to avoid the peak stress appearing in the second layer. A weak distal layer can reduce the distal stress of the foam under high-velocity impact, while a high density gradient between the last two layers will result in the early increase of the distal stress under moderate-velocity impact